The Influence of Total Assets, Total Debt, Total Equity and Total Sales on Net Profit In Cigarette Sub-Sector Companies Listed on the Indonesia Stock Exchange Period 2018-2022 - Utami, Wikan Budi; Utari Evy Cahyani; Suprihati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to determine and analyze the partial effect of total assets, total debt, total equity and total sales on net profit in cigarette sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2018 to 2022. This type of research is quantitative research. The data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is the quantitative descriptive method. The results obtained from this study conclude that partially total assets, total equity, and total sales have a significant effect on net profit in cigarette sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. While total debt does not have a significant effect on net profit in cigarette sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. Keywords: Assets, Debt, Equity, Sales, Net Profit